Curcumol Exerts Anticancer Effect in Cholangiocarcinoma Cells via Down-Regulating CDKL3 - Zhang, Jinduo; Su, Gang; Tang, Zengwei; Wang, Li; Fu, Wenkang; Zhao, Sheng; Ba, Yongjiang; Bai, Bing; Yue, Ping; Lin, Yanyan; Bai, Zhongtian; Hu, Jinjing; et al. (Frontiers in Physiology, 2018)
Curcumol is the major component extracted from root of Rhizoma Curcumae. Recent studies have shown that curcumol exerts therapeutic effects against multiple conditions, particularly cancers. However, the therapeutic role and mechanism of curcumol against cholangiocarcinoma cells are still unclear. In our current research, we tested the effect of curcumol in cholangiocarcinoma cells, and using two-dimensional electrophoresis, proteomics and bioinformatics, we identified cyclin-dependent kinase like 3 (CDKL3) as a potential target for curcumol. We have demonstrated that curcumol can evidently suppress growth and migration of cholangiocarcinoma cells. Furthermore, curcumol could significantly block the cell cycle progression of the cholangiocarcinoma cells. These effects could be largely attributed to the inhibition of CDKL3 by curcumol. Further studies have recapitulated the oncogenic role of CDKL3 in that knockdown of CDKL3 by lentiviral mediated transfection of shRNA against CDKL3 also led to a significant inhibition on cell proliferation, migration, invasion, and cell cycle progression. Given the high level of CDKL3 expression in human cholangiocarcinoma tissues and cell lines, we speculated that CDKL3 may constitute a potential biological target for curcumol in cholangiocarcinoma.